DiOHF Protects Against Doxorubicin-Induced Cardiotoxicity Through ERK1 Signaling Pathway - Chang, Danqi; Li, Hang; Qian, Cheng; Wang, Yanggan (Frontiers in Pharmacology, 2019)
Doxorubicin (DOX) is an effective anticancer agent. Its clinical use is, however, limited due to its detrimental side effects, especially the cardiotoxicity caused by ROS, mitochondrial dysfunction and apoptosis. 3’,4’-dihydroxyflavonol (DiOHF) is a recently developed potent synthetic flavonoid which has been reported to exert anti- oxidative activity in myocardial ischemia-reperfusion injury and maintain the normal mitochondrial function. The aim of this study was to explore the protective effects of DiOHF on the DOX-induced cardiotoxicity. We established DOX-induced cardiotoxicity in H9C2 cells by incubation with 1 μM DOX and in BALB/c mice by DOX injection. DiOHF effectively prevented and reversed the DOX-induced cardiotoxicity, including ROS production, mitochondrial dysfunction, and apoptosis. The DOX-induced cardiotoxicity was accompanied by ERK1/2 activation and abolished by the silence of ERK1, rather than ERK2. Furthermore, DOX treatment in mice induced an increase in serum CK-MB level and myocardial fibrosis with a reduction in left ventricular (LV) function. These detrimental effects were blunted by DiOHF administration. Conclusion: DiOHF suppresses and reverses the DOX-induced cardiotoxicity by inhibiting ROS release, stabilizing mitochondrial function and reducing apoptosis through activation of the ERK1 signaling.